Effect of the ACTN-3 gene polymorphism on functional fitness and executive function of elderly - Henrique, Jessica Salles; Braga, Pedro Luiz Garcia; Almeida, Sandro Soares de; Nunes, Nathalia Santanna Petraconi; Benfato, Izabelle Dias; Arida, Ricardo Mario; de Oliveira, Camila Aparecida Machado; Gomes da Silva, Sérgio (Frontiers in Aging Neuroscience, 2022)
During aging, physical integrity and cognitive abilities, especially executive function, become compromised, directly influencing the quality of life of elderly. One good strategy to ensure healthy aging is the practice of physical exercises. Activities to improve aerobic capacity and muscle strength are extremely important in old age. However, some genetic factors can interfere both positively and negatively in these gains. In this context, the polymorphism rs1815739 (R577X) of the α-actinin 3 gene (ACTN-3) is commonly studied and related to muscle phenotype. Thus, the present study aimed to investigate the effect of the ACTN-3 gene polymorphism on the functional fitness (measured by the Senior Fit test) and cognitive capacity (evaluated by the Stroop test) of elderly (n=347), both man and woman. We did not find effect of genotype on functional fitness, but it was observed a positive effect of ACTN-3 gene polymorphism on the executive function. The presence of the X allele of ACTN3 gene in elderly was related to a better performance in the Stroop test (shorter answer time). Our results showed that ACTN-3 gene polymorphism affects the executive function of elderly, but not the functional fitness.